Analysis of nonequilibrium atomic and molecular nitrogen radiation in pure N2 shockwaves. (November 2022) - Tibère-Inglesse, Augustin; Cruden, Brett A.
Highlights: Chemical and thermal equilibrium is not achieved 5 cm/120 µs away from the shock front. Nitrogen atoms follow a Boltzmann distribution. Differences between rotational temperatures of different species are observed, as well as differences between rotational and vibrational temperatures. Predissociation affects the C 3 Π u state of N2 . Abstract: This paper presents an analysis of data previously reported from a test series in the Electric Arc Shock Tube Facility for incident shocks composed of pure nitrogen. The present work focuses on the lowest velocity measured in the test (approximately 7 km/s) where both molecular and atomic radiation are significant. Analysis of the spectral data with the NEQAIR radiative transport code obtains post-shock trends in temperature and number densities of the states of N2 and atomic N. The results suggest that chemical, and possibly thermal, equilibrium has not been obtained within the distance/time measured (about 5 cm/80 µs). In the nonequilibrium region of the shock, differences between rotational temperatures of different species are observed, as well as differences between rotational and vibrational temperatures. Population of rotational states above the dissociation limit is observed to occur over a distance of several cm. Finally, these data suggest that predissociation strongly affects the C 3 Πu state of N2, leading to a lower measured radiation than predicted. An effective average pre-dissociation rate is shown to produce reasonable agreement under quasi-steady state approximation.